Metabolism of the anthelmintic drug fenbendazole in Arabidopsis thaliana and its effect on transcriptome and proteome - Syslová, Eliška; Landa, Přemysl; Raisová Stuchlíková, Lucie; Matoušková, Petra; Skálová, Lenka; Szotáková, Barbora; Navrátilová, Martina; Vaněk, Tomáš; Podlipná, Radka (Chemosphere, 2019)
Fenbendazole, a broad spectrum anthelmintic used especially in veterinary medicine, may impact non-target organisms in the environment. Nevertheless, information about the effects of fenbendazole in plants is limited. We investigated the biotransformation of fenbendazole and the effect of fenbendazole and its metabolites on gene expression in the model plant Arabidopsis thaliana. High-sensitive UHPLC coupled with tandem mass spectrometry, RNA-microarray analysis together with qPCR verification and nanoLC-MS proteome analysis were used in this study. Twelve fenbendazole metabolites were identified in the roots and leaves of A. thaliana plants. Hydroxylation, S-oxidation and glycosylation represent the main fenbendazole biotransformation pathways. Exposure of A. thaliana plants to 5 μM fenbendazole for 24 and 72 h significantly affected gene and protein expression. The changes in transcriptome were more pronounced in the leaves than in roots, protein expression was more greatly affected in the roots at a shorter period of exposure (24 h) and in leaf rosettes over a longer period (72 h). Up-regulated (>2-fold change, p < 0.1) proteins are involved in various biological processes (electron transport, energy generating pathways, signal transduction, transport), and in response to stresses (e.g. catalase, superoxide dismutase, cytochromes P450, UDP-glycosyltransferases). Some of the proteins which were up-regulated after fenbendazole-exposure probably participate in fenbendazole biotransformation (e.g. cytochromes P450, UDP-glucosyltransferases). Finally, fenbendazole in plants significantly affects many physiological and metabolic processes and thus the contamination of ecosystems by manure containing this anthelmintic should be restricted.
Keywords: kořeny rostlin; Plant Roots; Arabidopsis Proteins; Arabidopsis; Transcriptome; proteomika; Proteome; anthelmintika; proteiny huseníčku; regulace genové exprese u rostlin; Proteomics; Gene Expression Regulation, Plant; proteom; listy rostlin; Anthelmintics; transkriptom; Fenbendazole; fenbendazol; Plant Leaves